The Use of Image Media in Junior High School Poetry Writing Skills - Putra, Ikhsan Achmadi; Kusumaningsih, Dewi; Eli Rustinar; Ira Yuniati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
Images can be used as a medium in poetry writing skills. This research focuses on image media in improving the ability of junior high school students to write poetry. The purpose of this study explain the skills of writing poetry using image media. The results of this study are (1) The use of image media can be a poetry writing tool for students (2) Describe the role of teachers in learning to write poetry (3) Explain the obstacles faced by teachers in learning to write poetry (4) Explain obstacles for students to write poetry in class. This research data is in the form of information from interviews about poetry writing skills in Junior High School (SMPN) 09 Bengkulu city. This study involved educators and students at Junior High School (SMPN) 09 Bengkulu City. This study used techniques, observation, interviews, and documentation. This study used a descriptive qualitative approach.